Meningkatkan Hasil Belajar Matematika Materi Penjumlahan Pecahan Menggunakan Model Pembelajaran Problem Based Learning (PBL) Pada Kelas V SDN Pasar Lama 6 Banjarmasin - Syahida Rahmawati; Sunarno (CV. ITTC INDONESIA, 2024)
The problem in this study is the low learning outcomes of fifth-grade students in Mathematics, specifically in the addition of fractions. The causes include an uninteresting learning atmosphere, one-way teaching methods, and minimal student involvement, which lead to boredom and difficulty in understanding the material. The researcher provides a solution to this problem by using the Problem-Based Learning (PBL) model. This study employs classroom action research as its method, which is qualitative. The types of information presented in this study include subjective and quantitative data. Qualitative data were collected through observation sheets on teacher and student activities during the teaching and learning process, while quantitative data were obtained from students' learning outcomes through written tests at the end of each meeting. This research was conducted at SDN Pasar Lama 6 Banjarmasin during the 2023-2024 academic year, in the even semester of grade V. After two cycles, the results showed that teacher activity reached a score of 20 with the criteria